Evaluation of a lateral flow device for in-field detection of Banana Xanthomonas Wilt and its application in tracking the systemicity of Xanthomonas campestris pv. musacearum - Karamura, Georgina; Ochola, Dennis; Smith, Julian; Kubiriba, Jerome; Karamura, Eldad (African Journal of Agricultural Research, 2016)
Early detection of Banana Xanthomonas Wilt (BXW) in the field and immediate destruction of infected plants or plant tissue are key control methods to prevent the introduction and spread of BXW. This requires rapid, cost-effective and an on- site diagnostic tool to detect the bacterium, Xanthomonas campestris pv musacearum (Xcm). Polymerase chain reaction (PCR) detection technique for BXW is efficient but requires expensive equipment and knowledgeable expertise; this limits PCR application to the laboratory. This study therefore was carried out to evaluate the enzyme-linked immunosorbent assay (ELISA) tool configured as a lateral flow device (LFD) for detection of Xcm. Studies on the systemicity of Xcm in banana were carried out using the BXW-LFD in a field trial of 300 banana plants of Pisang Awak inoculated with the Xcm at Kiifu Forest, Mukono District, Uganda. Pseudo-stem samples from symptomatic and asymptomatic suckers were collected and tested with the LFD and the results compared with conventional PCR using the GspDm BXW primers. The LFD was able to detect Xcm 3 days post inoculation (dpi), 2 cm above and below inoculation site, 15 to 35 days in the pseudo-stem, 35 to 42 days to reach the corm and 81 days in the lateral roots. The rate of Xcm movement in banana was found to be sigmoid in nature, leveling off as the bacteria moved down the pseudo-stem towards the corm. Conventional PCR was only 24% more sensitive than the LFD. The use of the BXW LFD can therefore boost BXW control measures through improved surveillance and quarantine services to arrest the introduction and spread of the disease within and between national borders.
Keywords: Banana Xanthomonas Wilt lateral flow device (BXW LFD); Banana Xanthomonas wilt; Xanthomonas campestris pv musacearum; Complete systemicity; Incomplete systemicity; Lateral flow device